Development of a Point of Sale (POS) System for the Digitalization of Sales Transaction Recording Based on AI (Case Study: PT XYZ) - Erin Limanda Afriana; Dwi Fatrianto Suyatno (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2026)
Manual sales transaction management remains a common challenge for many small and medium-sized enterprises (SMEs), including PT XYZ, which still relies on physical receipts and handwritten recapitulation to record sales transactions. This condition increases the risk of recording errors, delays in data recapitulation, and difficulties in generating structured sales reports. This study aims to develop a web-based Point of Sale (POS) system integrated with an AI-based chatbot through Telegram and n8n workflow automation to support the digitalization of sales transaction records at PT XYZ. The system was developed using the Rapid Application Development (RAD) method, while data were collected through literature studies, observations, and interviews with the business owner. The developed system is capable of digitizing historical transactions through receipt data extraction using an AI chatbot while simultaneously supporting real-time transaction recording through a web-based POS system integrated into a centralized database. The black-box testing results indicate that all main system features operated according to user requirements, including product management, transaction recording, receipt digitization, and sales report generation. The implementation of the system improved transaction recording efficiency, minimized the risk of data loss, and produced more structured and accessible sales data. The findings demonstrate that the integration of AI chatbots and POS systems can serve as an effective sales transaction digitalization solution for SMEs.